Business Implications of Using Virtual Currency Exchange (Bitcoin) in Commercial Transactions - Iskamto, Dedi (ADPEBI, 2024)
Virtual currencies such as Bitcoin and Ethereum have seen a rapid increase in their use over the past few years. Their speed, security, and minimal transaction costs have attracted worldwide attention as a new alternative in commercial transactions. Therefore, this study aims to explore the business implications of using virtual currencies in commercial transactions. This study will analyze how virtual currencies affect various aspects of business such as payments, financial management, and relationships with third parties. On the other hand, the use of virtual currencies also brings some business challenges such as price volatility and lack of mature regulations related to virtual currencies. Using a systematic literature review method, this study will provide insights into how virtual currencies can change the way businesses operate and interact with customers.